Online organizer / Nur Julina Mohamad Nor - Nur Julina, Mohamad Nor (2004)
This project is about the development of a web-based organizer system. It began with an early research that covers the finding and gathering of information about the system. Then, scheduling the developing process and doing analysis on the system's requirements and design. Coding, implementing, testing and minimising come after that. Simultaneously, discussion about the problems faced and possible bugs found would be conducted, plus preparing a complete documentation of project. Overall, the whole project required one to understand the concept that lies behind a system development. Self-discipline. determination, literal thinking, decision-making and time management would be the elements to ensure its success. The application is the best way to boost productivity and simplify our life. It integrates three functions: Contact Manager, Calendar Manager, Personal Information Manager. User can use this system to store records of daily task, event, contacts and thoughts. furthermore, these key features can be instantly access with a colorful toolbar to enhance the application user friendliness. It also enables people to keep data and manage it in a more secure and efficient way. With the current popularity and expansion or the Internet. web based applications become new platform for the organizer system. The user can use the application as long as connection to "web server and database server. All sons of related information involve the online organizer were deeply analyzed and research had been done into the subject. In The analysis phase a questionnaire survey was conducted on 40 random samples to determine the requirement of the system. In reviewing the tools to fulfill such requirement, Active Server Pages (ASP). Hypertext Markup Language (HTM L). Dynamic Hypertext Markup Language (DHTML), JavaScript & VBScript are deemed most appropriate to develop the system. Building an effective system is about more that just technology but it takes me to exercising critical thinking skills too.